Catalyst free synthesis of poly(l‐lactic acid)–poly(propylene glycol) multiblock copolymers and their properties. Issue 37 (28th May 2017) - Jiang, Ziyan; Chang, Yue; Chen, Zhize
ABSTRACT: A simple, green, and economical method for the synthesis of poly(l ‐lactic acid)–poly(propylene glycol) (PLLA–PPG) copolymers is put forward and a series of multiblock PLLA–PPG are synthesized with 1, 6‐hexamethylene diisocyanate as chain extender of the melt polymerization. The effect of PPG content on the properties of PLLA–PPG copolymers is also investigated. The elongation at break of the resulting copolymer film with only 5% weight content PPG is 280%, and the tensile strength is 20 MPa. Dynamic mechanical analysis results demonstrated the existence of the shape memory effect for all the copolymers films and the shape recovery ratio of 101% is achieved for PLLA–PPG copolymer film with 5% weight PPG. The process for the synthesis of PLLA–PPG copolymers in the total absence of potentially toxic solvents and catalysts is analyzed, and the films of PLLA–PPG exhibit toughness and shape memory effect. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45299. Abstract :